Credit Risk Management Strategy in Clothing Installment Business to Maintain Social Value and Business Sustainability - Febriayu, Lelita; Atika, Atika; Yanti, Nursantri (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to analyze the risk management strategies for non-performing loans (NPLs) in informal clothing instalment businesses in rural areas, focusing on the role of social values and the adaptation of the 5C theory. Using a qualitative embedded case study, research was conducted on a 15-year-old clothing installment enterprise in Padang Langkat Village serving 72 customers from vulnerable households. Data were collected through in-depth interviews, 12 weeks of participant observation, and analysis of instalment records, WhatsApp chats, and collection photos. The results showed ex-ante strategies in the form of customer selection based on social reputation, evaluation of informal payment capacity, and structured manual recording. Ex-post strategies included a familial approach, phased collection, personal visits, and instalment restructuring. Social capital in the form of trust, norms, and social networks played a role in replacing formal collateral and reducing NPLs by up to 6.9%. The conceptual contribution of this research is the social adaptation of the 5C theory, with an emphasis on Character and Conditionfactors, while Collateral is replaced by social security, emphasizing the importance of local cultural context in the sustainability of informal micro-enterprises.